Studying the Electrical Conductivity of Different Carbon Fillers Reinforced Polyvinyl Chloride Composite Materials - Abed Al ameer, Nirvana A.; Jameel, Walla W.; Hassan, Nagham S. (Nahrain University College of Engineering Journal, 2013)
The aim of this study is development the electrical conductivity of composite materials which used three fillers of carbon reinforced PVC at different weight fractions. The experimental results showed that carbon black was more effective than carbon fiber and synthetic graphite at low weight fractions, it reached (0.229 S/cm) whereas it was (0.109 S/cm) and (0.104 S/cm) of each carbon fiber and synthetic graphite respectively. At (40%) weight fraction the electrical conductivity was increased to (0.216 S/cm) and (0.226 S/cm) of each carbon fiber and synthetic graphite while it was inattentive with carbon black. Hybrid composites were investigated also; the result appears that maximum value of the electrical conductivity at combination of (20%) weight fraction of fillers, it was (0.592 S/cm).